2018
DOI: 10.1111/jan.13580
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking working conditions for health and safety in the frontline healthcare industry: Perspectives from Australia and Malaysia

Abstract: We move toward a better understanding of the precursors of psychosocial safety climate in a broader context, including similarities and differences between Australia and Malaysia in national culture, government occupational health and safety policies and top-level management practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…28 However, the PSC construct has been used widely across a range of different samples demonstrating similar relationships. [55][56][57][58] In this study, PSC was also used as a continuous measure and showed similar results.…”
Section: Limitationssupporting
confidence: 55%
“…28 However, the PSC construct has been used widely across a range of different samples demonstrating similar relationships. [55][56][57][58] In this study, PSC was also used as a continuous measure and showed similar results.…”
Section: Limitationssupporting
confidence: 55%
“…Because nurses generally tend to be exposed to higher levels of job demands than many other workers (Hu et al, 2016), nurses can be expected to present higher levels of global and specific (cognitive weariness, physical fatigue, and emotional exhaustion) burnout and/or be overrepresented into profiles characterized by the highest levels of burnout across dimensions (e.g., a High Burnout profile), when compared to mixed employees. For instance, McLinton et al (2018) showed that Australian health care workers (including registered nurses) displayed significantly higher levels of burnout (M = 4.27 on a seven-point scale ranging from 1 to 7) than a general community sample of employed Australians (M = 3.17). Similarly, Malaysian health care workers were characterized by higher levels of burnout (M = 4.07) than a general community sample of private sector Malaysian workers (M = 2.64).…”
Section: Profile Similarity Across Samplesmentioning
confidence: 99%
“…This result is consistent with previous studies that suggest healthcare accreditation standards are generally considered an important benchmark for the attributes of healthcare professionals to improve clinical safety practice. 43 However, the evidence about whether accreditation standards significantly change healthcare professional’s safety behaviors with the effect of safety climate and safety attitudes is equivocal and determined by circumstances such as psychosocial working conditions, 44 national culture, 45 and government health and safety policies. 46…”
Section: Discussionmentioning
confidence: 99%